Mass spectrometry of polyurethanes. (24th October 2019) - Crescentini, Tiffany M.; May, Jody C.; McLean, John A.; Hercules, David M.
Abstract: This review covers the applications of mass spectrometry (MS) and its hyphenated techniques to characterize polyurethane (PU) synthetic polymers and their respective hard and soft segments. PUs are commonly composed of hard segments including methylene bisphenyl diisocyanate (MDI) and toluene diisocyanate (TDI), and soft segments including polyester and polyether polyols. This literature review highlights MS techniques such as electrospray ionization (ESI), matrix assisted laser/desorption ionization (MALDI), ion mobility-mass spectrometry (IM-MS), and computational methods that have been used for the characterization of this polymer system. Here we review specific case studies where MS techniques have elucidated unique features pertaining to the makeup and structural integrity of complex PU materials and PU precursors. Graphical abstract: Image 1081 Highlights: Combination of MS-based techniques used to characterize PUs and their precursors. Characterization techniques such as ESI, MALDI, IM-MS, and computational methods to interpret the data. Inclusion of various separation strategies in combination with MS, including GC, LC, and IM.